PURIFICATION AND CHARACTERIZATION OF PEROXIDASE FROM MORINGA OLEIFERA L. LEAVES - Shahanaz Khatun,; Md. Ashraduzzaman,; Md. Rezaul Karim,; Farzana Pervin,; Nurul Absar,; Ahmad Rosma (BioResources, 2012)
Peroxidase catalyzes the oxidation of various electron donor substrates such as phenol and aromatic amines in the presence of hydrogen peroxide. In this study, peroxidase was purified 164-fold from the leaves of Moringa oleifera L. with a recovery of 28% by ammonium sulphate precipitation, DEAE-cellulose column chromatography, Sephadex G-200 column chromatography, and Con-A column chromatography. SDS-PAGE showed a polypeptide band with molecular weight of 43 kDa. The enzyme was found to be a single subunit in nature. The purified enzyme displayed optimum activity at pH 6.0 and at a temperature of 50 °C with a Km value of 0.2335 mM for guaiacol as best substrate. It is a glycoprotein that contains 9.05% sugar as estimated by the phenol sulfuric acid method. Some ions (Ni2+, Pb2+, Zn2+, Al3+, Mg2+, Cu2+, Co2+, and Cd2+) exhibited low inhibitory effect while Fe2+, Fe3+, and Hg2+ exhibited strong inhibitory effects. EDTA markedly inhibited the peroxidase activity.